Combined Effects of Biochar and Rhamnolipid on Phenanthrene Biodegradation in Agricultural Soil: Bioavailability and Microbial Community Dynamics - Meng Zhang; Yuke Kang; Jie Ran; Jichao Song; Zhongyi Wang; Jiawang Li; Liyuan Chen (Agriculture)
The present study investigated the combined effects of wheat straw biochar (BC) and biosurfactant rhamnolipid (RL) on the biodegradation kinetics of phenanthrene by indigenous microorganisms in agricultural soil, focusing on dynamic responses of both bioavailability and community structure. The combined treatment (BC + RL, 60.63%) significantly enhanced phenanthrene biodegradation compared to RL alone (54.74%) and the control (45.98%), while BC amendment alone (42.55%) notably inhibited biodegradation by reducing phenanthrene bioavailability despite increasing bacterial abundance, enzyme activity, and community diversity. Both RL and BC + RL treatments promoted bioavailability by transforming phenanthrene from tightly bound (very slowly desorbing fraction, Fvslow) to readily bioavailable fractions (rapidly and slowly desorbing fractions, Frapid and Fslow), as revealed by sequential Tenax extraction. The RL-mediated increase in phenanthrene bioavailability to microbes by 11.93–17.90% via solubilization greatly enriched PAH-degrading bacterial genera and the nidA gene, contributing to enhanced biodegradation. The BC + RL combination outperformed the single application of RL in improving phenanthrene biodegradation due to their synergy in stimulating microbial population and activity (e.g., Bacillus, Massilia, Sphingomonas, and polyphenol oxidase) as a growth stimulus. These findings demonstrate that BC and RL co-application enhances PAH removal through improved bioavailability and optimized microbial communities, offering a promising strategy for soil bioremediation to ensure agricultural product safety.